Produksi Bokashi Limbah Ternak Kerbau sebagai Sumber Pupuk Organik untuk Meningkatkan Pertumbuhan Bibit Gaharu (Aquilaria Malaccensis L.) - Lisa Ruben Dannari; Emar Deliyanti Tolayuk; Yusuf L. Limbongan; Sepsriyanti Kannapadang; Willy Yavet Tandirerung; Golindira Randa (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study aims to determine the effect of buffalo waste bokashi on the growth of agarwood seedlings and the economic value of buffalo waste bokashi business. This study was conducted at the Malimbong Balepe agricultural extension center, Tana Toraja Regency, South Sulawesi, from August to December 2025. The study was conducted using a randomized block design (RAK) with 4 treatment levels, namely; B0 (without bokashi), B1 (200 grams/plant), B2 (400 grams/plant), and B3 (600 grams/plant). The parameters observed were plant height, number of leaves, stem diameter, and root volume. Data were analyzed using a combined analysis of variance (ANOVA), while for farming business analysis using the R/C ratio, Break Event Point (BEP) and Return On Investment (ROI). The results showed that the B3 treatment (600 grams/plant) was the best treatment for plant height, leaf number, stem diameter, and root volume. The buffalo waste bokashi business had an R/C ratio of 2,80, ROI 180% indicating that this business is feasible.